(0.10x+22)+(0.1x-21)+(0.3x+23)=

Simple and best practice solution for (0.10x+22)+(0.1x-21)+(0.3x+23)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (0.10x+22)+(0.1x-21)+(0.3x+23)= equation:


Simplifying
(0.10x + 22) + (0.1x + -21) + (0.3x + 23) = 0

Reorder the terms:
(22 + 0.10x) + (0.1x + -21) + (0.3x + 23) = 0

Remove parenthesis around (22 + 0.10x)
22 + 0.10x + (0.1x + -21) + (0.3x + 23) = 0

Reorder the terms:
22 + 0.10x + (-21 + 0.1x) + (0.3x + 23) = 0

Remove parenthesis around (-21 + 0.1x)
22 + 0.10x + -21 + 0.1x + (0.3x + 23) = 0

Reorder the terms:
22 + 0.10x + -21 + 0.1x + (23 + 0.3x) = 0

Remove parenthesis around (23 + 0.3x)
22 + 0.10x + -21 + 0.1x + 23 + 0.3x = 0

Reorder the terms:
22 + -21 + 23 + 0.10x + 0.1x + 0.3x = 0

Combine like terms: 22 + -21 = 1
1 + 23 + 0.10x + 0.1x + 0.3x = 0

Combine like terms: 1 + 23 = 24
24 + 0.10x + 0.1x + 0.3x = 0

Combine like terms: 0.10x + 0.1x = 0.2x
24 + 0.2x + 0.3x = 0

Combine like terms: 0.2x + 0.3x = 0.5x
24 + 0.5x = 0

Solving
24 + 0.5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-24' to each side of the equation.
24 + -24 + 0.5x = 0 + -24

Combine like terms: 24 + -24 = 0
0 + 0.5x = 0 + -24
0.5x = 0 + -24

Combine like terms: 0 + -24 = -24
0.5x = -24

Divide each side by '0.5'.
x = -48

Simplifying
x = -48

See similar equations:

| 12t+-8=-52 | | 2.5x+10=x-.5 | | (350n)-(30n+125n+700)=1055 | | 2y+0=10 | | -16-8k=-6k-2(k+8) | | f(-1)=1--1+1 | | 8(n-5)+7(1-8n)=-33 | | 119=-7(3x-2) | | 11(x-1)=7x+25 | | 8.3=-0.5-2.7 | | -16+x=-x-4 | | 7x=6x+8 | | 3(x+1)+6+3y=2x | | -16x+x=-x-4 | | 3x+7=2x-6forx | | 8(3x-2)+3=2x+1 | | 8(p+6)= | | 550-5x=250+10x | | 18=-2(-4)+b | | 2y+15=10 | | -3(8+8k)=168 | | 5+4n=8+4n | | 2(5n+2)=8n-4 | | 368=8(8b+6) | | 17+1c=14 | | 7x^2y+(-10xy)+7xy+(-6xy^2)= | | 25-4p=-7 | | 2y+-15=10 | | -1+8(8a+5)=-26-a | | 4t-6-3t=t-7 | | -10=1x-6 | | 5a-9-3=18 |

Equations solver categories